PEMBERDAYAAN MASYARAKAT MELALUI BUDIDAYA AYAM POTONG SKALA RUMAH TANGGA DI KOTA KENDARI - Rizki, Selvi Diliyanti; Agustina, Wa Ode (Jurnal Pengabdian Masyarakat Berkarya, 2024)
Broiler farming has great potential to improve household income and support local food security in Kendari City, Southeast Sulawesi. However, many small-scale farmers face challenges such as limited knowledge of modern farming techniques, high feed costs, and poor marketing access. The title of this Community Service is Community Empowerment Through Household Scale Slaughter Chicken Farming in Kendari City. This community empowerment program aims to provide training and mentoring on efficient broiler farming practices, including feed management, disease prevention, and simple business planning. The methods include workshops, hands-on training, and the formation of farmer groups to strengthen collective marketing. The expected outcomes are increased productivity and income for participating farmers, reduced production costs through local feed alternatives, and the establishment of a sustainable small-scale poultry business model. This initiative aligns with the government’s efforts to promote economic independence and food security at the household level.